Effects of Ant (Formica subsericea) Nests on Physical and Hydrological Properties of a Fine‐Textured Soil. Issue 2 (29th March 2016) - Drager, Kim I.; Hirmas, Daniel R.; Hasiotis, Stephen T.
Abstract : Core Ideas: Chemical changes of ant nests extend beyond nest boundaries. Ants may utilize vertic cracks in soil for transport during dry years. Ant nest biopores are important conduits for water in fine‐textured soil. Ants are known to preferentially line subsurface nest components with coarser or finer material and may expand or backfill areas as colony size expands and contracts. These modifications may contribute to significant redistribution of soil material, leading to changes in soil physical and hydrological properties. A total of 102 small‐volume (∼1 cm 3 ) soil samples were taken from the surface mound, near individual subsurface nest components, and in soils within 1 m of two Formica subsericea colonies to determine how ants affect soil bulk density, organic C content, and particle‐size distributions. Overall, the surface mound had higher soil organic C and silt contents than the rest of the nest, soil near galleries in the upper horizons had higher bulk density, and soil near chambers in the lower horizons had higher C values. Ant‐modified soil properties extended beyond the extent of the surface mound and could be seen up to 1 m away. Cracks exacerbated by the vertic properties of the surrounding soil provided higher surface area for C mineralization and spaces for ants to travel through, which could explain the lower bulk density outside the nest if ants modify interpedal pore spaces during dry periods. Modeling results from the soils in this study showed that soils with ant‐modified properties were associated with more rapid increases and decreases in moisture content than the control soil (i.e., unmodified by ants). Physical and chemical alterations of ant‐modified soil diminish with increasing depth, as nest structures decrease in density.